Pengaruh Ownership Retention, Reputasi Auditor, Laba Perusahaan, dan Underpricing terhadap Nilai Perusahaan dengan Kepemilikan Manajerial dan Institusional Sebagai Variabel Pemoderasi - Barbara Gunawan; Mazda Halim (Journal of Accounting and Investment, 2012)
This research aims to examine the effect of ownership retention (OR), auditor's reputation, company's profit and underpricing on the value of the firm after an initial public offering and the moderating effect of managerial ownership and institutional ownership variables on the relationship between the proportion of retained ownership with value of the firm after the initial public offering. The samples of this research were 60 companies that run IPO (Initial Public Offering) and are listed in Indonesia Stock Exchange (IDX) from 2008 to 2011. The research samples used purposive sampling method.The data used in this research are secondary data which consist of prospectus financial report, fact book, and other supporting references. The data analysis technique was classical assumption test: normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The hypothesis test used multiple regression analysis. The result of this research shows that: the proportion of shares ownership that is still owned by old owners and auditor's reputation has a positive effect to the company's value after an initial public offering. Managerial and institutional ownership do not moderate the relationship between the proportions of shares ownership which are still owned by old owners with the company's value after an initial public offering.